Designers approach in managing legal design risks in Malaysia / Zul Zakiyuddin Ahmad Rashid, Hamimah Adnan and Norazian Mohd Yusuwan - Ahmad Rashid, Zul Zakiyuddin; Adnan, Hamimah; Mohd Yusuwan, Norazian (Faculty of Architecture, Planning & Surveying, 2015)
Design risk is one of various risk elements in a construction works. Exploring the understanding of Malaysian professional designers on design related risks, risk management, laws related to the management of such risks as well as the sufficiency of existing laws to the effect is the objective of the research. Quantitative research method was applied, where questionnaire survey was adopted to collect data from professional designers, consist of professional architects and engineers. The data were then analysed using SPSS software. The finding reveals that the respondents were in consensus in certain areas, such as the importance to understand the law, but were in mix of opinion with regards to some area such as the branches of law regulating their duty. It is concluded that, understanding of professional designers on design risks, risk management and the laws can be further improved.